Understanding the document selection rationale of Library and Information Science students. (2nd January 2018) - Kumar, Vinit; Pandey, Rahul
Abstract : Purpose: The study aims to investigate the document selection rationale of library and information science students to satisfy their academic needs. Design/methodology/approach: The descriptive survey design was used for the study using questionnaire as the data collection instrument. The collected data are analysed by frequency distribution and presented using charts and tables. Findings: The results of the study reveal the preferences of Library and Information Science (LIS) students and hints what they want from LIS literature. A majority of students prefer books in comparison to journal articles as reading material. The survey revealed a high preference towards books written by authors from national origin than international authors. Similarly, students prefer books published by the national publishers than the international publishers. The findings further suggest that the affiliation of the author is a major factor, as the students prefer books written by authors from central universities more than those written by authors belonging to state universities or authors from industry. Further, students seem to be more impressed with the books written by LIS academics than the books written by practising librarians. Research limitations/implications: One limitation of the study is that it was conducted in India, taking the case of LIS students from only two universities. To generalise the impact, similar studies should be replicated by taking a larger sample to gain a complete perspective of LIS students. Practical implications: The findings of the study have both theoretical and practical implications. The theoretical understanding of the behaviour of LIS students will help faculty members to understand the selection rationale of students. The practical aspect of this study is that the findings will help the acquisition librarians to take informed decisions in collection building for LIS collection in their libraries. Originality/value: Most of the studies available in LIS literature related to reading preferences, study the general aspects such as frequency of library visit, the favourite place of reading, the purpose of library visit, gender-wise distribution of library visit, and time spent in the library. There are very few studies investigating the document selection rationale of LIS students.